ANALISIS DAMPAK PERILAKU BULLYING TERHADAP HASIL BELAJAR MATA PELAJARAN IPS DI SD - Miftakhul Amalia Kurnia Susanto; Iva Sarifah; Chrisnaji Banindra Yudha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study examines the impact of bullying behavior on the learning outcomes of Social Science (IPS) at the elementary school level. Employing a qualitative approach and literature review, this research explores how physical, verbal, and social bullying affects classroom interactions and students' academic performance. The findings indicate that bullying significantly reduces students' participation in class discussions and group activities, essential for effective learning in IPS. This not only impedes academic understanding but also hinders the development of social skills such as empathy and cooperation. The case of Yurika is highlighted as a case study to emphasize society's response to bullying disclosures and its impact on the victims. The study recommends the implementation of comprehensive strategies in education to address bullying, creating a safe and supportive learning environment in schools.